The Storm Before the Calm? Adverse Effects of Tackling Organised Crime - Iain W. Long (Cardiff University, Cardiff Business School, 2014)
Policies targeted at high-crime neighbourhoods may have unintended consequences in the presence of organised crime. Whilst they reduce the incentive to commit crime at the margin, those who still choose to join the criminal organisation are hardened criminals. Large organisations take advantage of this, substituting away from membership size towards increased individual criminal activity. Aggregate crime may rise. However, as more would-be recruits move into the formal labour market, falling revenue causes a reversal of this effect. Thereafter, the policy reduces both size and individual activity simultaneously.
Keywords: D82; J24; J28; K42; L21; 330; Organised crime; crime policy; occupational choice